Iron homeostasis and iron-regulated ROS in cell death, senescence and human diseases - Nakamura, Toshitaka; Naguro, Isao; Ichijo, Hidenori (Biochimica et biophysica acta. General subjects, 2019)
Iron is essential for many types of biological processes. However, excessive iron can be cytotoxic and can lead to many diseases. Since ferroptosis, which is an iron-dependent regulated form of necrosis, was recently discovered, iron and iron-catalysed oxidative stress have attracted much interest because of their sophisticated mechanism of cellular signalling leading to cell death and associated with various diseases. In this review, we first focus on how iron catalyses reactive oxygen species (ROS). Next, we discuss the roles of iron in cell death and senescence and, in particular, the downstream signalling pathways of ROS. Finally, we discuss the potential regulation mechanism of iron as a therapeutic target for various iron-related diseases. Both labile iron released from organelles upon various stresses and iron incorporated in enzymes produce ROS, including lipid ROS. ROS produced by iron activates various signalling pathways, including mitogen-activated protein kinase (MAPK) signalling pathways such as the apoptosis signal-regulating kinase 1 (ASK1)-p38/JNK pathway. These ROS-activated signalling pathways regulate senescence or cell death and are linked to cancer, ischaemia-reperfusion injury during transplantation and ageing-related neurodegenerative diseases. Iron overload damages cells and causes harmful effects on the body through oxidative stress. Thus, understanding the spatiotemporal availability of iron and the role of iron in generating ROS will provide clues for the suppression of ROS and cytotoxic redox-active iron. Moreover, elucidating the molecular mechanisms and signalling pathways of iron-dependent cytotoxicity will enable us to find novel therapeutic targets for various diseases. •Intracellular iron generates reactive oxygen species (ROS)•Iron-mediated ROS regulates various types of cell death and cellular senescence•Control of cellular iron levels could be a therapeutic target for several diseases